Implementasi Aplikasi Pemantauan dan Reservasi Layanan Laundry Self-Service Berbasis Mobile Menggunakan Metode Waterfall - Salma Mahzarena; Yuli Asriningtyas (Journal of Information System Research (JOSH), 2025)
In today's digital era, mobile application-based services have become essential for consumers, including in the realm of self-service laundry. One common challenge for users is the uncertainty of washing machine availability upon arriving at the location. This study aims to design and develop a mobile-based monitoring and reservation application for self-service laundry. The application was developed using Flutter for the mobile platform and Laravel for the backend, utilizing the Waterfall software development methodology. The application allows users to monitor real-time washing machine availability and reserve vacant machines, thereby reducing waiting times and improving service efficiency. Data collection was carried out through direct observation at laundry locations and a literature review related to reservation systems. The test results indicate that the application accurately provides machine availability information and simplifies the reservation process. In conclusion, the application enhances user convenience and satisfaction in using self-service laundry services.